Elucidating the processes affecting highly primitive lavas of the Borgarhraun flow (northern Iceland) using trace elements in olivine. (1st October 2020) - Tollan, Peter; Gurenko, Andrey; Hermann, Jörg
Abstract: Olivine is typically the first phase to crystallise from basaltic melts and its chemistry can therefore inform on the earliest stages of magmatic evolution, not recorded by later crystallising phases. Despite the potential of olivine for understanding primitive differentiation, limited analytical capabilities have previously restricted the range of elements that can be routinely measured. Consequently, important processes controlling early magma evolution may have been overlooked or misidentified. This study reports a wide range of minor and trace elements in forsteritic (up to Fo92.2 ) olivine macrocrysts from the primitive Borgarhraun lava flow in northern Iceland. We define two distinct populations of olivine based on their forsterite (Fo) content and then apply minor and trace element data to discern mixing and crystallisation of subtly different high-MgO parental melts. High-Fo (90.9–92.2 mol%) olivines show approximately linear trends between Cr and other incompatible trace elements (Li, Na, Ca, Ti, Al and Y), implying mixing and concurrent crystallisation of two highly primitive melts. Low-Fo (87.4–90.0 mol%) olivines show trends that indicate mixing and crystallisation of multiple, genetically distinct and less primitive melts. The outermost 50 μm of the olivine microcrysts record diffusive re-equilibration of the olivine macrocrysts to a single, significantly more evolved carrier liquid over an ascent timescale of 70–250 days. Compared to the rest of Iceland, the Borgarhraun olivine macrocrysts are distinguished by their Cr contents, which extend from 97 to 1150 ppm. The uniquely steep trend in Fo vs. Cr can be explained by early crystallisation of Cr-spinel and Cr-rich clinopyroxene, stabilised by high pressures of differentiation (>0.8 GPa). Chromium-forsterite systematics may therefore be a powerful tool for qualitatively assessing relative pressures of crystallisation for different magmatic systems. Collectively, our new dataset clearly demonstrates the importance of measuring trace elements in olivine for identifying the formative stages and conditions of basaltic magmatic systems.